Immunomodulatory agents lenalidomide and pomalidomide co-stimulate T cells by inducing degradation of T cell repressors Ikaros and Aiolos via modulation of the E3 ubiquitin ligase complex CRL4(CRBN.) - Gandhi, Anita K; Kang, Jian; Havens, Courtney G; Conklin, Thomas; Ning, Yuhong; Wu, Lei; Ito, Takumi; Ando, Hideki; Waldman, Michelle F; Thakurta, Anjan; Klippel, Anke; Handa, Hiroshi; et al. (British journal of haematology, 2014)
Cereblon (CRBN), the molecular target of lenalidomide and pomalidomide, is a substrate receptor of the cullin ring E3 ubiquitin ligase complex, CRL4(CRBN) . T cell co-stimulation by lenalidomide or pomalidomide is cereblon dependent: however, the CRL4(CRBN) substrates responsible for T cell co-stimulation have yet to be identified. Here we demonstrate that interaction of the transcription factors Ikaros (IKZF1, encoded by the IKZF1 gene) and Aiolos (IKZF3, encoded by the IKZF3 gene) with CRL4(CRBN) is induced by lenalidomide or pomalidomide. Each agent promotes Aiolos and Ikaros binding to CRL4(CRBN) with enhanced ubiquitination leading to cereblon-dependent proteosomal degradation in T lymphocytes. We confirm that Aiolos and Ikaros are transcriptional repressors of interleukin-2 expression. The findings link lenalidomide- or pomalidomide-induced degradation of these transcriptional suppressors to well documented T cell activation. Importantly, Aiolos could serve as a proximal pharmacodynamic marker for lenalidomide and pomalidomide, as healthy human subjects administered lenalidomide demonstrated Aiolos degradation in their peripheral T cells. In conclusion, we present a molecular model in which drug binding to cereblon results in the interaction of Ikaros and Aiolos to CRL4(CRBN) , leading to their ubiquitination, subsequent proteasomal degradation and T cell activation.